Phương pháp xây dựng miền ổn định robust - Lân, Lê Hùng (Journal of Computer Science and Cybernetics, 2016)
The problem of constructing a robust stability domain in parameter space is considered. The proposed technique is based on genelizating a classical D-partition method [1] for control system with uncertain parameters.